3(4-2x)+3=2(-3x+7)+1

Simple and best practice solution for 3(4-2x)+3=2(-3x+7)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4-2x)+3=2(-3x+7)+1 equation:



3(4-2x)+3=2(-3x+7)+1
We move all terms to the left:
3(4-2x)+3-(2(-3x+7)+1)=0
We add all the numbers together, and all the variables
3(-2x+4)-(2(-3x+7)+1)+3=0
We multiply parentheses
-6x-(2(-3x+7)+1)+12+3=0
We calculate terms in parentheses: -(2(-3x+7)+1), so:
2(-3x+7)+1
We multiply parentheses
-6x+14+1
We add all the numbers together, and all the variables
-6x+15
Back to the equation:
-(-6x+15)
We add all the numbers together, and all the variables
-6x-(-6x+15)+15=0
We get rid of parentheses
-6x+6x-15+15=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 3x+5-2x=-27+7x | | 8r-4=r+20+10r | | 7z+5+(-19)=53 | | 6+k=4+2k | | b−9=-2b | | 5(x-2)+3=-(x+4) | | 5(v-7)-8v=-26 | | 82-40x=2 | | 7k+3=4k | | 2x-5x-6.3=14.4 | | 3(d−75)=36 | | 2+9y=7y+2 | | 4x+50=-6x | | 14m+14-9m=3m-18 | | |3-7v|=59 | | 39x+2761x-36=56(50x+56) | | 4g=6g+10 | | 1+8v+7v=7v+1+8v | | 11k=-209 | | x=0.09+0.1x | | -8q+5=-9q | | -18+20s=s+18+17s | | 4-2(3-x)=0.2(6x+10) | | 4y+6=-2(2y+3) | | 10+3a=5 | | -9z=9-6z | | 0=16t^2-48t-2 | | 3(y+4)=60-y | | 13-13+15d=-20+14d | | 11x=24+9x | | X+5x=186 | | -24x=44 |

Equations solver categories